MANAJEMEN PENDIDIKAN ISLAM PADA SMA BERBASIS PESANTREN - Moh. Harun Al Rosid; Ilma Safira (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The purpose of this study was to determine the implementation, characteristics of Islamic education management based on pesantren in SMA Darussalam Blokagung Banyuwangi. The research method uses descriptive qualitative, data collection through interviews, observation and documentation. The paradigm of this research is postpositivistic with data analysis of three Miles and Huberman models, namely data reduction, data presentation and conclusion drawing. The results in this study are the implementation of Islamic boarding school-based education management through planning; with good service adopting the concept of modern school management, involving all stakeholders, organizing; grouping of work units according to school needs, implementation; creating effective communication, committed to implementing the school's vision, mission and values, supervision; determination of implementation standards, determination of measurement of the implementation of activities. Meanwhile, the characteristics of Islamic education management based on pesantren are having sincerity in teaching; high dedication in work, discipline in every activity, maintaining solidity by establishing friendship between teachers and employees, and maintaining trust and responsibility in carrying out each task.